Imaging Spontaneous Imbibition in Full Darcy‐Scale Samples at Pore‐Scale Resolution by Fast X‐ray Tomography. Issue 8 (22nd August 2019) - Bartels, W.‐B.; Rücker, M.; Boone, M.; Bultreys, T.; Mahani, H.; Berg, S.; Hassanizadeh, S. M.; Cnudde, V.
Abstract: Spontaneous imbibition is a process occurring in a porous medium which describes wetting phase replacing nonwetting phase spontaneously due to capillary forces. This process is conventionally investigated by standardized, well‐established spontaneous imbibition tests. In these tests, for instance, a rock sample is surrounded by wetting fluid. The following cumulative production of nonwetting phase versus time is used as a qualitative measure for wettability. However, these test results are difficult to interpret, because many rocks do not show a homogeneous but a mixed wettability in which the wetting preference of a rock varies from location to location. Moreover, during the test the flow regime typically changes from countercurrent to cocurrent flow and no phase pressure or pressure drop can be recorded. To help interpretation, we complement Darcy‐scale production curves with X‐ray imaging to describe the differences in imbibition processes between water‐wet and mixed‐wet systems. We found that the formation of a spontaneous imbibition front occurs only for water‐wet systems; mixed‐wet systems show localized imbibition events only. The asymmetry of the front depends on the occurrence of preferred production sites, which influences interpretation. Fluid layers on the outside of mixed‐wet samples increase connectivity of the drained phase and the effect of buoyancy on spontaneous imbibition. The wider implication of our study is the demonstration of the capability of benchtop laboratory equipment to image a full Darcy‐scale experiment while at the same time obtaining pore‐scale information, resolving the natural length and time scale of the underlying processes. Key Points: We demonstrate the capability of imaging full Darcy‐scale experiments while obtaining pore‐scale resolution In the mixed‐wet system there is a difference between pore scale and Darcy scale production due to oil layers on the sample perimeter Water‐wet systems show a clear imbibition front, whereas mixed‐wet systems show only localized imbibition sites